THE EFFECTIVE METHODS IN TEACHING FOREIGN LANGUAGES: WEB QUEST AND CASE STUDY - Yusupova Muhabbat, Yusupova Muhabbat (Журнал иностранных языков и лингвистики, 2021)
The use of case study in teaching foreign languages is one of the most effective ways to develop students' speaking skills. Case study involves the development of students' logical thinking as well as language skills. In addition, teachers can utilize web quest technology during the teaching process as a motivational tool to keep students on learning.